Dynamic Intermediate Waters Across the Late Glacial Revealed by Paired Radiocarbon and Clumped Isotope Temperature Records. Issue 7 (10th July 2019) - Hines, Sophia K. V.; Eiler, John M.; Southon, John R.; Adkins, Jess F.
Abstract: Paired radiocarbon and clumped isotope temperature records from U/Th‐dated Desmophyllum dianthus corals in the North Atlantic and Southern Ocean provide unique information about the history of intermediate waters (∼1, 500–1, 700 m) across the late glacial and deglaciation (∼35–10 ka). These measurements allow for the construction of radiocarbon‐temperature crossplots, which help to identify water mass endmembers at different times across the deglaciation. Radiocarbon and temperature values from the late glacial fall outside the range of modern ocean data from near the sample collection sites. In the North Atlantic, radiocarbon values tend to be much older than the modern, while in the Southern Ocean, they are more often younger than the modern. Reconstructed temperatures vary around respective modern ocean values; however, warm waters are observed at the Last Glacial Maximum and across the deglaciation in the north and south. We interpret our data in the context of the modern hydrography of the Western North Atlantic and Southern Ocean, and we draw upon direct comparisons between sediment core‐derived reconstructions of ocean circulation from the South Indo‐Pacific and our deep‐sea coral data from the Southern Ocean. Our North Atlantic data support accepted patterns of reduced North Atlantic Deep Water formation during Heinrich Stadials 1 and 2. In the Southern Ocean, deep‐sea coral populations respond to changes in ocean structure that are also reflected in a depth profile of δ 13 C data from New Zealand, and data indicate that there was less influence of Pacific Deep Water between 1, 500 and 1, 700 m south of Tasmania across much of the deglaciation. Key Points: Intermediate‐depth waters are highly dynamic throughout the late glacial ϵ 14 C and temperature crossplots from paired measurements show ocean endmembers across deglaciation Temperature and ϵ 14 C data are outside the range of modern data in the N. Atlantic and Southern Ocean